Peran Orangtua Dan Guru Pak Dalam Pembentukan Karakter Rohani Anak Di Sdn Cawang 01 Pagi, Jakarta Timur - Juni Wando Purba (Institut Agama Kristen Negeri (IAKN) Ambon, 2019)
The study aims to describe the role of PAK's parents and teachers in the formation of children's spiritual characters. The focus of this research is how PAK's parent and teacher roles are in the formation of child's spiritual character. Research was conducted at SDN Cawang 01 Pagi and as a source of data for children's parents, Guru PAK, and a Christian child. Data collection techniques consist of literature reviews, interviews, and documentation. The instruments in this research are interview guidelines, and are denomented. The data analysis technique used in this study is a qualitative data analysis, following the concepts given Miles and Huberman and Spradley. From the results of the analysis of data obtained the conclusion of the parent role in the formation of children's spiritual character in the school Cawang 01 morning, not entirely fulfilled. While the role of teachers PAK SDN Cawang 01 Pagi, has been done with the maximum, namely as educators, counselors, advisers, motivators, evangelists, communicators, and socialization agents and roles in accordance with the demands of the curriculum KTSP.Keyword: parents, master teacher, spiritual character